2022
DOI: 10.1007/s00467-022-05440-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relevance of NUP93 variants in steroid-resistant nephrotic syndrome using next generation sequencing and a fly kidney model

Abstract: Background Variants in genes encoding nuclear pore complex (NPC) proteins are a newly identified cause of paediatric steroid-resistant nephrotic syndrome (SRNS). Recent reports describing NUP93 variants suggest these could be a significant cause of paediatric onset SRNS. We report NUP93 cases in the UK and demonstrate in vivo functional effects of Nup93 depletion in a fly (Drosophila melanogaster) nephrocyte model. Methods Three hundred thirty-seven paedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Our data are consistent with previous reports [ 5 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], highlighting NUP93 variants as a cause of paediatric-onset SRNS. Interestingly, the individual described is heterozygous with two different variants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are consistent with previous reports [ 5 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], highlighting NUP93 variants as a cause of paediatric-onset SRNS. Interestingly, the individual described is heterozygous with two different variants.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, NUP93 , expressed in all kidney cell types [ 5 ], is involved in NPC assembly, and its mutations are the direct cause of the complex disruption triggering a distinct renal disease [ 6 ]. To date, 21 different NUP93 mutations are reported in 22 SRNS patients, with the most common variant, c.1772G>T, present in almost half of the described cases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report by Braun et al, numerous mutations in NUP93 (Fig. 3, Table 1) have been identified in patients with SRNS or focal segmental glomeruloscelerosis (FSGS; MIM 603278), a precursor state of SRNS [73][74][75][76][77][78][79][80][81][82]). In SRNS, podocytes, specialised epithelial cells that line the nephrons of the kidney, are mainly affected.…”
Section: Nephrotic Syndromesmentioning
confidence: 99%
“…Both cell types contain highly specialized filtration structures know as slit diaphragms that act in concert with the basement membrane; the fly lacuna channel is similar to the urinary space in the mammalian Bowman’s capsule; and, many key proteins for podocyte function are likewise essential for nephrocyte function (van de Leemput et al, 2022; Wang et al, 2021; Weavers et al, 2009; Zhuang et al, 2009). Indeed, fly in vivo nephrocyte models have been successfully used to study a variety of human kidney diseases, including forms of monogenic nephrotic syndrome and steroid-resistant nephrotic syndrome (SRNS) (Ashraf et al, 2013; Bierzynska et al, 2022; Fu et al, 2017; Gee et al, 2015, 2013; Gonçalves et al, 2018; Hermle et al, 2018, 2017; Milosavljevic et al, 2022; Odenthal et al, 2023; Paul et al, 2023; Zhao et al, 2019; Zhu et al, 2017). The recent study using the HFD Drosophila model recapitulated the ectopic lipid droplets and cellular dysfunction observed in chronic kidney disease and found that the adipose-derived triglyceride lipase protects nephrocyte endocytosis under HFD conditions (Lubojemska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%